2018
DOI: 10.1002/acp.3380
|View full text |Cite
|
Sign up to set email alerts
|

Co‐thought gestures in children's mental problem solving: Prevalence and effects on subsequent performance

Abstract: SummaryCo-thought gestures are understudied as compared to co-speech gestures yet, may provide insight into cognitive functions of gestures that are independent of speech processes. A recent study with adults showed that co-thought gesticulation occurred spontaneously during mental preparation of problem solving. Moreover, co-thought gesturing (either spontaneous or instructed) during mental preparation was effective for subsequent solving of the Tower of Hanoi under conditions of high cognitive load (i.e., wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
1
1
0
1
Order By: Relevance
“…Gestures seem to be especially productive for problem-solving performance when tasks are more complex (corroborating the previous findings, Chu & Kita, 2008), and interact with visual (but not spatial) working-memory capacity. Moreover, instructing others to do so may aid problem-solving performance (at least for adult problem solvers; see Pouw, Van Gog, Zwaan, Agostinho, & Paas, 2018). The present study, therefore, provides an additional support that gestures' cognitive function may go beyond speech processing and provides the initial insight into improving educational environments by soliciting embodied problem solving.…”
Section: Resultssupporting
confidence: 54%
“…Gestures seem to be especially productive for problem-solving performance when tasks are more complex (corroborating the previous findings, Chu & Kita, 2008), and interact with visual (but not spatial) working-memory capacity. Moreover, instructing others to do so may aid problem-solving performance (at least for adult problem solvers; see Pouw, Van Gog, Zwaan, Agostinho, & Paas, 2018). The present study, therefore, provides an additional support that gestures' cognitive function may go beyond speech processing and provides the initial insight into improving educational environments by soliciting embodied problem solving.…”
Section: Resultssupporting
confidence: 54%
“…Thus, it is possible that when narrating a cartoon (i.e., describing visuospatial information that was observed rather than performed), children gesture less than adults because the visuospatial imagery of the cartoon does not automatically activate their motor systems to the same degree as it does in adults. In contrast, when the task involves thinking about actions that one has performed oneself, there may be no differences in the gesture rates of children and adults, as research with problem-solving tasks has shown (Pouw, van Gog, Zwaan, Agostinho, & Paas, 2018).…”
Section: Gestures Are Designed For the Listenermentioning
confidence: 99%
“…Çocukların erken yaşlardan itibaren problem çözme becerilerinin desteklenmesi, çocuğun gerçek yaşama uyum sağlamasını kolaylaştırdığı belirtilmekte ve özellikle okul öncesi eğitimin problem çözme becerileri üzerinde etkisi olduğu vurgulanmaktadır (Kelley, 2018). Çocuğa problem çözme için fırsat verildiğinde, çocuğun gözlem, karşılaştırma, bilgiyi değerlendirme, düzenleme gibi bilişsel yetenekleri geliştirdiği (Pouw, Van Gog, Zwaan, Agostinho ve Paas, 2018) gibi demokratik tutum ve davranışları da desteklenmektedir (Fawcett ve Garton, 2005).…”
unclassified